The Value of Lakota Traditional Healing for Youth Resiliency and Family Functioning. Issue 5 (27th May 2016) - Freeman, Brenda J.; Coll, Kenneth M.; Two Dogs, Rick; Iron Cloud Two Dogs, Ethleen; Iron Cloud, Eileen; Robertson, Paul
ABSTRACT: This article reports research findings on the impact of Oglala Lakota Sioux traditional healing on family functioning and youth resiliency where trauma, abuse, or violence are often present. Caregivers of Lakota youth struggling with serious emotional and behavioral problems participated in the study. The study included both quantitative and qualitative samples: 27 families for the quantitative sample and 8 families for the qualitative sample. Results from caregivers revealed that traditional healing and cultural practices, as well as the promotion of cultural identity, had statistically significant positive effects on the perceived familial and individual functioning of Lakota youth and their families. Effect sizes indicate that the results have strong practical significance.